Psychrotolerant Strains of Phoma herbarum with Herbicidal Activity - Andrey Trigubovich; Maryna Mandryk-Litvinkovich; Anastasiya Valakhanovich; Elizaveta Gorodilova; Daniil Malygin; Emiliya Kalamiyets; Sofia Sokornova (Agronomy, 2023)
The search for stress-tolerant producer strains is a key factor in the development of biological mycoherbicides. The aim of the study was to assess the herbicidal potential of phoma-like fungi. Morphological and physiological features of two Antarctic psychrotolerant strains 20-A7-1.M19 and 20-A7-1.M29 were studied. Multilocus sequence analysis was used to identify these strains. They happened to belong to Phoma herbarum Westend. The psychrotolerant properties of these strains were suggested not only by ecology, but also by their capability to grow in a wide temperature range from 5 °C to 35 °C, being resistant to high insolation, UV radiation, aridity, and other extreme conditions. It was shown that treatment with their cell-free cultural fugate, crude mycelium extract, and culture liquid significantly reduced the seed germination of troublesome weeds such as dandelion and goldenrod. Cell-free cultural fugate and culture liquid also led to the formation of chlorosis and necrotic spots on leaves. Thus, psychrotolerant strains P. herbarum 20-A7-1.M19 and 20-A7-1.M29 demonstrate high biotechnological potential. Our next step is to determine the structures of biologically active substances and to increase their biosynthesis, as well as the development of biological and biorational mycoherbicides. New mycoherbicides can reduce the chemical load on agroecosystems and increase the effectiveness of applied chemicals.